Cell Volume Changes and Membrane Ruptures Induced by Hypotonic Electrolyte and Sugar Solutions - Božič, Bojan; Zemljič Jokhadar, Špela; Kristanc, Luka; Gomišček, Gregor (Frontiers in Physiology, 2020)
The cell volume changes induced by hypotonic electrolyte and sucrose solutions were studied in Chinese-hamster-ovary epithelial cells. The effects in the solutions with osmolarities between 32 and 315 mOsm/L, and distilled water were analyzed using bright-field and fluorescence confocal microscopy. The changes of the cell volume, accompanied by the detachment of cells, the formation of blebs and the occurrence of almost spherical vesicle like-cells (“cell-vesicles”) showed significant differences in the long-time responses of the cells in the electrolyte solutions compared to the sucrose containing solutions. A theoretical model based on different permeabilities of ions and sucrose molecules, and on the action of Na+/K+-ATPase pumps is applied. It is consistent with the observed temporal behavior of the cells’ volume and the occurrence of tension-induced membrane ruptures, and explains lower long-time responses of the cells in the sucrose solutions.